Identificação e Classificação de Patologias em Pavimentos Rodoviários Flexíveis e Rígidos Utilizando YOLOv8 - Monte, Danillo Marcus Farias Marinho do; Goldschmidt, Ronaldo Ribeiro; Santos, Marcos dos (Proceedings of the Brazilian Symposium on Multimedia and the Web (WebMedia), 2025)
Road pavement infrastructure plays a fundamental role in mobility and economic development, with Brazil having over 213,500 km of paved roads. However, conventional inspection methods for pavement pathologies are predominantly manual, subjective, costly, and pose risks to evaluators. Recent advances in Deep Learning, particularly Convolutional Neural Networks (CNNs), have emerged as promising alternatives for automatic defect identification through computer vision. A systematic literature review identified 209 studies published between 2019-2024, revealing that most existing work focuses exclusively on flexible pavements, leaving gaps in rigid pavement pathology detection. Hence, this study proposes a hybrid model based on the YOLOv8 neural network for automatic identification and classification of pathologies in both flexible and rigid pavements. The proposed model incorporates a BACKbone + CSPNet architecture that reduces computational costs without compromising performance. The methodology involved collecting approximately 4,000 images using a customized approach with Go-Pro cameras equipped with GPS across different Brazilian regions under various climatic conditions, followed by manual annotation of 1,000 images for training. The model achieved promising results with mAP50 of approximately 90%, precision up to 96%, and mean Pixel Accuracy of 88%. An extra validation was conducted on 65 road segments of 1 km each across three Brazilian regions, where 51 segments with various pathologies were successfully identified and classified.